Meningkatkan Keterampilan Gerak Tari Melalui Strategi Praktik Berpasangan Kelas IV SD Negeri 66/IV Kota Jambi - D Destrinelli; L Leony (Jurnal Gentala Pendidikan Dasar, 2019)
Abstract. This study aims to describe the application of paired practice strategies (Practice Rehearsal Pairs) to improve dance movement skills of students in 4th grade elementary school dance learning. This research was conducted in 66 / IV Public Elementary School in Jambi City in the even semester of the 2018/2019 academic year. This type of research is classroom action research, which consists of II cycles with procedures starting from planning, implementation, observation, and reflection. The subjects of this study were grade IVB students of SD 66 / IV in Jambi City. Instrument Data collection used was teacher action observation and practice test (performance) of student dance movement skills. Data were analyzed qualitatively and quantitatively. The results of the percentage of student practice tests (performance) amounted to 45% with less categories in the first cycle and increased in the second cycle by 82.5% in the good category. From the results of this study, it was concluded that by implementing a paired practice strategy (Practice Rehearsal Pairs) can improve students' dance skills in fourth grade elementary school dance learning. Keywords: Practice Rehearsal Pairs, dance movements skills